PELAKSANAAN PERATURAN DAERAH NOMOR 4 TAHUN 2011 TENTANG PAJAK REKLAME DI KOTA PEKANBARU - Novia Tesa; Emilda Firdaus; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Advertisement tax is a tax on the implementation of the billboard. Implementation of the advertisement tax is regulated on Regional Regulation Nu. 4 in 2011 on Advertisement Tax in Pekanbaru City. In Article 1 point (13) the taxpayer is an individual or entity that organizes advertisement. It is means the Advertisement Entrepreneur is obliged to pay the advertisement tax. But the reality in the field, many Organizer Advertisement Tax do not pay taxes. This is causes a reduction of the original income Pekanbaru City in 2015.Regional Regulation Nu. 4 in 2011 on Advertisement Tax in the Pekanbaru City. The Second, obstacles in the implementation of Regional Regulation No. 4 of 2011 on Advertising tax in Pekanbaru, The Third, efforts should be made to overcome the obstacles Implementation of Regional Regulation No. 4 in 2011 on Advertisement Tax in Pekanbaru CityKeywords:Implementation-Tax- Advertising